Doctoring the Country House: Edward Wrench and Chatsworth. (4th May 2019) - Beardmore, Carol
Abstract : This article explores the role of Edward Wrench in doctoring Chatsworth House. He purchased the practice in Baslow in 1862 and from the beginning sought to become the doctor of choice for the Devonshire family when in residence and the numerous staff that they employed. Edward Wrench's diaries which exists in an unbroken run until his death in 1912 create a prism through which to explore the country house and its consumption history from a different angle. It will examine the importance of men like the Duke of Devonshire in establishing a practice both in the medical marketplace and within society. While the local GP might call in a consultant when conditions appeared to be anything other than minor this did not mean that they did not play an important role in the health of an aristocratic family and their staff. Overall it gives a sense of the conditions suffered and treated locally. More importantly for a young GP setting up in practice and gaining the trust of a wealthy patient could mean the difference between success and failure. While historians have explored the evolution of General Practice, the historiography remains short of detailed case studies and this article will start to fill this gap.